Free Radical Scavenging Activity, Tyrosinase Inhibition Activity and Fatty Acids Composition of Oils from Pupae of Native Thai Silkworm (Bombyx mori L.) - Supanida Winitchai; Jiradej Manosroi; Masahiko Abe; Korawinwich Boonpisuttinant; Aranya Manosroi (Agriculture and Natural Resources, 2011)
Oils were extracted from five native Thai silkworm varieties, Keaw Sakon, Nangnoi Srisaket, Sam Rong, Nang Luang and None Ruesee. The yields of the oils by the Soxhlet and maceration methods were in the ranges 24–29 and 5–7%, respectively. Oils extracted from None Ruesee by the Soxhlet method, and oils extracted from Nang Leung, Sam Rong and None Ruesee by the maceration method showed free radical scavenging activity. Oil extracted from None Ruesee by the maceration method gave the highest free radical scavenging activity. Moreover, oil extracted by the Soxhlet method from None Ruesee gave the highest tyrosinase inhibition activity, but was lower than that of standards of vitamin C and kojic acid. The silkworm pupae oil obtained from Soxhlet extraction had unsaturated fatty acid content in the range 72–79% and alpha-linolenic acid content in the range 32–44%, whereas that obtained from the maceration extraction had unsaturated fatty acid content in the range 75–80% and alpha-linolenic acid content in the range 40–46%. The study indicated that oil from native Thai silkworm pupae could be used as an alternative in the food and cosmetic industries.